Development of a Three-dimensional Hydrogel System for the Maintenance of Porcine Spermatogonial Stem Cell Self-renewal - Ji Eun Park; Min Hee Park; Min Seong Kim; Jung Im Yun; Jung Hoon Choi; Eunsong Lee; Seung Tae Lee (The Korean Society of Animal Reproduction and Biotechnology, 2017)
Porcine spermatogonial stem cells (SSCs) prefer three-dimensional (3D) culture systems to 2D ones for the maintenance of self-renewal. Of the many 3D culture systems, agar-based hydrogels are candidates for supporting porcine SSC self-renewal, and there are various types of agar powder that can be used. In this study, we sought to identify an agar-based 3D hydrogel system that exhibited strong efficacy in the maintenance of porcine SSC self-renewal. First, 3D hydrogels with different mechanics were prepared with various concentrations of Bacto agar, lysogeny broth (LB) agar, and agarose powder, and the 3D hydrogel with the strongest alkaline phosphatase (AP) activity and greatest increase in colony size was identified for the different types of agar powder. Second, among the porcine SSCs cultured in the different 3D hydrogels, we analyzed the colony formation, morphology, and size; AP activity; and transcription and translation of porcine SSC-related genes, and these were compared to determine the optimal 3D hydrogel system for the maintenance of porcine SSC self-renewal. We found that 0.6% (w/v) Bacto agar-, 1% (w/v) LB agar-, and 0.2% (w/v) agarose-based 3D hydrogels showed the strongest maintenance of AP activity and the most pronounced increase in colony size in the culture of porcine SSCs. Moreover, among these hydrogels, the strongest transcription and translation of porcine SSC-related genes and largest colony size were detected in porcine SSCs cultured in the 0.2% (w/v) agarose-based 3D hydrogel, whereas there were no significant differences in colony formation and morphology. These results demonstrate that the 0.2% (w/v) agarose-based 3D hydrogel can be effectively used for the maintenance of porcine SSC self-renewal.